Ritual Kaefoilaha Ndoke (Mengusir Monyet) pada Kebun Desa Liabalano Kecamatan Kontunaga Kabupaten Muna - Herlina Haluru; Syahrun Syahrun; Rahmat Sewa Suraya (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
The Kaefoilaha Ndoke ritual is a ritual carried out in a garden that has been planted with various kinds of plants which are the source of the community's survival, but now it is starting to be abandoned. This study aims to describe the implementation process, function and to analyze the meaning contained in the Kaefoilaha Ndoke ritual in the garden. The method in this research is descriptive qualitative. The results showed that there are three implementation processes, namely, the preparation stage of tools and materials, the implementation stage such as cutting and splitting ginger, wrapping ginger using corn husks, kaefoilaha ndoke, and planting ginger. The three final stages are: storing water bottles in the kafematai and sprinkling them around the garden. There are three functions of the kaefoilaha ndoke ritual, namely preservation, religion, and the function as a lifeline.